2017
DOI: 10.1111/lam.12740
|View full text |Cite
|
Sign up to set email alerts
|

Fermented cereal beverages: from probiotic, prebiotic and synbiotic towards Nanoscience designed healthy drinks

Abstract: There is currently a great interest in producing healthy food in particular that which has an impact in improving the gastrointestinal health such as probiotics, prebiotics and synbiotics. Most of these functional foods are dairy based and have been greatly accepted worldwide. Nevertheless, there has been a need for the development of nondairy probiotic, prebiotic and synbiotic products. This has encouraged food scientists to study the feasibility of applying other fermenting substrates such as cereals for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(43 citation statements)
references
References 74 publications
1
42
0
Order By: Relevance
“…Despite the importance of gut microbiota in host health, the gut microbiota are not constant. Their structures are changed by host development, diet and habitat (Bletz et al., ; Salmerón, ; Schwartz et al., ; Wang et al., ). Analysing the effects of changes in the host habitat on gut microbiota is still a main research focus (Falony et al., ; Stappenbeck & Virgin, ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the importance of gut microbiota in host health, the gut microbiota are not constant. Their structures are changed by host development, diet and habitat (Bletz et al., ; Salmerón, ; Schwartz et al., ; Wang et al., ). Analysing the effects of changes in the host habitat on gut microbiota is still a main research focus (Falony et al., ; Stappenbeck & Virgin, ).…”
Section: Introductionmentioning
confidence: 99%
“…Xylooligosaccharide has only been recently regarded as a new class of prebiotics and has been proven to be more effective in a range of health benefits and gut flora composition at lower doses compared to oligosaccharides FOS or inulin (Pan et al . ; Salmerón ; Linares‐Pasten et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…The results of clinical studies proved the positive effect of probiotics and prebiotics on human gastrointestinal system and numerous diseases such as allergic diseases, obesity, insulin resistance syndrome, type 2 diabetes, hypertension, coronary heart disease, nonalcoholic fatty liver disease, and cancer and its side effects (Markowiak and Sli_ zewska, 2017;Salmer on, 2017). Thus, the global interest in fermented functional beverages rich in prebiotics and probiotics has been increasing continuously (Altay et al, 2013;Marsh et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the global interest in fermented functional beverages rich in prebiotics and probiotics has been increasing continuously (Altay et al, 2013;Marsh et al, 2014). The health benefits of boza are attributed to its (i) probiotic LAB, (ii) prebiotics originated from exopolysaccharides (EPS) produced by LAB (Heperkan et al, 2014) and (iii) cereal dietary fibre (Prado et al, 2008;Todorov et al, 2008;Vasudha & Mishra, 2013;Heperkan et al, 2014;Dogan & Ozpinar, 2017;Petrova & Petrov, 2017;Salmer on, 2017). Kancabas ß & Karakaya (2013) also reported that boza is also a good source for bioactive peptides with antihypertensive activity.…”
Section: Introductionmentioning
confidence: 99%